The Design of a Gamified App for Supporting Undergraduates' Resilience - Nicolaidou, Iolie; Aristeidis, Loizos (My University, 2022)
Supporting students in building psychological resilience is crucial considering the COVID-19 pandemic’s effect on the population’s mental health. Psychological resilience refers to finding ways to cope with stress and achieve goals despite obstacles. It is an important life skill that has become highly relevant in the post-pandemic era. Mobile devices and applications are becoming integral to users’ self-monitoring of health data for their access, convenience, and cost advantages. Most resilience apps target specific professional groups, are not gamified, and lack solid theoretical foundations. Phone-based sensor data collected using Internet of Things (IoT) technology allow for new ways to measure psychological health and provide personalized recommendations. However, none of the existing gamified apps on resilience used IoT. None of the existing resilience apps refers to behavioral change techniques. The proposed resilience app addresses these gaps in the literature. This paper describes the design of a prototype for a gamified, theory-based mobile app that utilizes IoT to provide personalized data and support undergraduates’ resilience in the “new normal” of the pandemic. The poster also provides preliminary data on undergraduates' feasibility and usability evaluation of the prototype, focusing on first-year students. Users set one of three goals daily (focusing on studying, engaging in physical exercise, and socializing), monitor their progress towards achieving them, and receive points and badges when reaching their goals. Goal setting, progress monitoring, and self-reflection at the end of each day are connected to a) self-reported data (e.g., through the use of a short, validated mental health survey that automatically calculates users’ level of anxiety) and b) objectively measured data through the use of IoT (accelerometer and noise sensors) in the app. Users can share their badges on their social media networks.Thirty first-year undergraduates (M=18.41 years old, SD=0.57) tested the prototype resilience app and completed an evaluation questionnaire examining feasibility and usability. Neutral to positive responses (M=3.32 out of 5) were received for all functions indicating feasibility. Design usability was evaluated as satisfactory (System Usability Score=70.3). Future research will evaluate the app in a quasi-experimental setting. Implications for the design of gamified mobile apps for health are drawn.
Keywords: COVID-19 pandemic; higher education; design for social change; gamified applications; resilience